A multi gene-approach genotyping method identifies 24 genetic clusters within the genotype II-European African swine fever viruses circulating from 2007 to 2022 - Gallardo, Carmina; Casado, Nadia; Soler, Alejandro; Djadjovski, Igor; Krivko, Laura; Madueño, Encarnación; Nieto, Raquel; Perez, Covadonga; Simon, Alicia; Ivanova, Emiliya; Donescu, Daniel; Milicevik, Vesna; et al. (Frontiers Media SA, 2023)
African swine fever (ASF) is a contagious viral disease of pigs and wild boar that poses a major threat to the global swine industry. The genotype II African swine fever virus (ASFV) entered the European Union (EU) in 2014 and since then fourteen countries have been affected, Italy and North Macedonia being the last in 2022. While whole genome sequencing remains the gold standard for the identification of new genetic markers, sequencing of multiple loci with significant variations could be used as a rapid and cost-effective alternative to track outbreaks and study disease evolution in endemic areas.